Analysis of the Results of Ginger and Beras kencur for increasing Breast Milk Production - Epi Saptaningrum; Cipto Cipto; Ajeng Titah Normawati (Jurnal Studi Keperawatan, 2022)
Background: The period of breastfeeding is a period of development in the human life cycle, in which the mother experiencing postpartum lactation period that has been born. In the period of breastfeeding, postpartum mothers experience a variety of problems related to breastfeeding. One of the problems that often arise and are found in women during lactation ahead of today is about the production of milk. All women experience postpartum lactation future. Along with the development of technology and science, traditional medicine related to an increase in milk production is also not forgotten. Objective: This study aimed to determine differences in the effect of buffoonery and rice kencur to lactation in Blora district Method: This research was quasy Experiment and design research with post test only control group design. The population is postpartum mothers a number of 54 respondents were divided into three (3) groups: 18 respondents were given treatments concoction of ginger, 18 respondents were given treatments kencur herb rice and 18 respondents were not given treatments. Results: The analysis used is a statistical test of Kruskal-Wallis test. Giving temulawak and beras kencur equally affect the smoothness of breastfeeding on postpartum mother, but the most dominant influence on lactation on postpartum mother is the provision of beras kencur And sig: 0.00. Of the mean (average) and sig is 0.05, it can be interpreted that after being given a different treatment is true. Keywords: Temulawak; saffron-coloared rice ; increased milk production